QUO VADIS NILAI-NILAI DASAR UNDANG-UNDANG BADAN HUKUM PENDIDIKAN: Tantangan dan Peluang bagi Pengelolaan Pendidikan Tinggi - Moh. Muslih (Jurnal Forum Tarbiyah, 2010)
This paper will focus on discussion of various basic valuesor principles that form the basis and foundation in managing highereducation as stipulated in Law No. 9 of 2009 on Legal Education(BHP) established on December 17, 2009.In the context of higher education autonomy, the principlesimplemented are: autonomy, accountability, transparency, qualityassurance, excellent service, fair access, diversity, sustainability, andparticipation on state responsibility in the administration of highereducation are expected to answer a variety of educational issuesthat still being hold back.Thus, the management of higher education in Indonesia in the future,is expect to be moremanaged, more profesional and able to make aneducation management system that is effective and efficient toimprove quality, quality and competitiveness